2014
DOI: 10.1039/c4ra05843g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled triphenylamine derivative for trace detection of picric acid

Abstract: Detection of explosives is of utmost importance due to the threat to human security as a result of illegal transport and terrorist activities. Picric acid (PA) is widely used in the industrial and military fields, and is inadvertently able to contaminate the environment and groundwater, posing a threat to human health.Achieving the detection of explosives at the parts per billion (ppb) level using chemosensors is a great challenge. Herein, we demonstrate that triphenylamine based fluorescent chemosensors tris(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…S6 and S7). 56 Furthermore, the PL decay curves shown in Fig. S8 suggest comparable lifetimes (6.48 vs. 5.77 μs) of Th-SINAP-200 and H 3 TCBPA, confirming the ligand-based emission of Th-SINAP-200.…”
supporting
confidence: 62%
“…S6 and S7). 56 Furthermore, the PL decay curves shown in Fig. S8 suggest comparable lifetimes (6.48 vs. 5.77 μs) of Th-SINAP-200 and H 3 TCBPA, confirming the ligand-based emission of Th-SINAP-200.…”
supporting
confidence: 62%
“…17) for the detection of picric acid in the solution phase as well as in the vapour phase. 99 For both probes, the fluorescence emission intensity rapidly decreased upon the addition of increasing amounts of PA solution, but, interestingly, the quenching efficiencies of 67 and 68 toward PA were found to be 82% and 95%, respectively. From scanning electron microscopy (SEM) images, the authors found that the interactions of 67 and 68 with PA, possibly through multiple hydrogen bonds, lead to breakdown in the assembly morphology of 67 and 68 .…”
Section: Fluorescent Probes Based On a Triphenylamine Platform For Ne...mentioning
confidence: 92%
“…In the static mechanism, the lifetime of the luminescent probe will remain unchanged due to the formation of a non‐emissive ground state complex through the bonding between the luminescent probe and the quencher (PA). In the dynamic quenching mechanism, the lifetime will be reduced due to the electron transfer between the excited state luminescent probe and the quencher (PA) . To explore the quenching mechanism, we measured the photoluminescence lifetime of the luminescent nanocrystals before (2.84 ms) and after (1.02 ms) the addition of PA.…”
Section: Methodsmentioning
confidence: 99%